2008
DOI: 10.1901/jaba.2008.41-629
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contribution of Economic Valence to Contingency Management Efficacy: A Pilot Study

Abstract: We investigated the extent to which a contingency management (CM) procedure that deducted money from a grand total available at the end of the study compared to a procedure in which money accumulated with continued abstinence from cigarette smoking. Results suggested that the procedure in which money increased contingent on abstinence resulted in a significantly greater likelihood of obtaining a clinically relevant (i.e., 48-hr) period of abstinence. In terms of attendance, participants in the condition in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 8 publications
3
21
0
Order By: Relevance
“…Using this approach, we found that participants worked less for cocaine in the $3-equivalent conditions than $1 condition. Several studies that evaluated effects of schedules of reinforcement on behavior maintained by nicotine (Roll et al, 1996; Roll and Higgins, 2000; Roll and Howard, 2008) and methamphetamine (Roll and Shoptaw, 2006) found that escalating schedules of non-drug reinforcement reduce drug choice to a greater extent than fixed schedules. Together, these studies confirm that economic gain reduces drug-maintained responding not only as a function of magnitude, but also when effort required to earn the economic reinforcer escalates.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, we found that participants worked less for cocaine in the $3-equivalent conditions than $1 condition. Several studies that evaluated effects of schedules of reinforcement on behavior maintained by nicotine (Roll et al, 1996; Roll and Higgins, 2000; Roll and Howard, 2008) and methamphetamine (Roll and Shoptaw, 2006) found that escalating schedules of non-drug reinforcement reduce drug choice to a greater extent than fixed schedules. Together, these studies confirm that economic gain reduces drug-maintained responding not only as a function of magnitude, but also when effort required to earn the economic reinforcer escalates.…”
Section: Discussionmentioning
confidence: 99%
“…First, basic and applied research has shown that punitive consequences produce side effects, including avoidance of the context in which the punishment occurs and/or the individuals who are administering consequences 136,137. Thus, in the context of an incentive-based intervention for healthy behavior, fines or other punitive consequences may have a negative impact on patients’ relationships with treatment providers or may cause patients to disengage with treatment 138140. Second, unlike rewards, which are often most effective when delivered intermittently, punitive consequences should be delivered following each occurrence of unhealthy behavior to ensure efficacy 141,142.…”
Section: Consequencesmentioning
confidence: 99%
“…Please see Table 1 for incentive schedule. The value of incentives for both attendance and abstinence escalated incrementally to encourage both study retention and achievement of longer periods of continuous abstinence (Roll and Howard, 2008; Roll and Shoptaw, 2006). Participants were told that they would revert to the initial attendance payment level ($5) following a missed study visit and that they would be discontinued from the study if abstinence was not confirmed.…”
Section: Methodsmentioning
confidence: 99%